Engineered hyaluronic acid-decorated niosomal nanoparticles for controlled and targeted delivery of epirubicin to treat breast cancer. (December 2022) - Mansoori-Kermani, Amirreza; Khalighi, Sadaf; Akbarzadeh, Iman; Niavol, Fazeleh Ranjbar; Motasadizadeh, Hamidreza; Mahdieh, Athar; Jahed, Vahid; Abdinezhad, Masoud; Rahbariasr, Nikoo; Hosseini, Mahshid; Ahmadkhani, Nima; Panahi, Behnam; et al.
Abstract: Targeted drug delivery systems using nanocarriers offer a versatile platform for breast cancer treatment; however, a robust, CD44-targeted niosomal formulation has not been developed and deeply studied (both in vitro and in vivo ) yet. Here, an optimized system of epirubicin (Epi)-loaded niosomal nanoparticles (Nio) coated with hyaluronic acid (HA) has been engineered for targeting breast cancer cells. The nanoformulation was first optimized (based on size, polydispersity index, and entrapment efficiency); then, we characterized the morphology, stability, and release behavior of the nanoparticles. Epirubicin release from the HA-coated system (Epi-Nio-HA) showed a 21% (acidic buffer) and 20% (neutral buffer) reduction in comparison with the non-coated group (Epi-Nio). The cytotoxicity and apoptosis results of 4T1 and SkBr3 cells showed an approximately 2-fold increase in the Epi-Nio-HA system over Epi-Nio and free epirubicin, which confirms the superiority of the engineered nanocarriers. Moreover, real-time PCR data demonstrated the down-regulation of the MMP-2, MMP-9, cyclin D, and cyclin E genes expression while caspase-3 and caspase-9 gene expression were up-regulated. Confocal microscopy and flow cytometry studies uncovered the cellular uptake mechanism of the Epi-Nio-HA system, which was CD44-mediated. Furthermore, in vivo studies indicated Epi-Nio-HA decreased mice breast tumor volume by 28% (compared to epirubicin) without side effects on the liver and kidney. Conclusively, our results indicated that the HA-functionalized niosomes provide a promising nanoplatform for efficient and targeted delivery of epirubicin to potentially treat breast cancer. Graphical abstract: After optimizing the formulation of epirubicin-loaded niosomes, the optimized nanoparticles were coated with hyaluronic acid to provide active targeting and more efficient delivery. Image 1